2011
DOI: 10.1016/j.vaccine.2011.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of novel nanoparticle-coated MSP-1 C-terminus malaria DNA vaccine using different routes of administration

Abstract: (Vaccine 29 (2011)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Therefore, the DGL/γ-PGA complexes examined in the present study might have accumulated in the spleen via the same mechanism. We previously reported that a pDNA/polyethylenimine/γ-PGA complex, which also induced strong gene expression in the spleen, was an effective DNA vaccine against malaria [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the DGL/γ-PGA complexes examined in the present study might have accumulated in the spleen via the same mechanism. We previously reported that a pDNA/polyethylenimine/γ-PGA complex, which also induced strong gene expression in the spleen, was an effective DNA vaccine against malaria [25].…”
Section: Discussionmentioning
confidence: 99%
“…An effective delivery system for malaria vaccination has been described for an NP-coated, MSP-1 DNA-based vaccine which confers protection against lethal Plasmodium yoelii infection in mouse models across various routes of administration. 55 Molecular adjuvants for malaria DNA vaccines based on the modulation of host-cell apoptosis have been described. 56 Field literature describes Vaxfectin (Vical, USA) as having the ability to elevate antibody response and T cell response to each component of a 5-gene Plasmodium falciparum plasmid DNA vaccine mixture.…”
Section: Dna Vaccine and Malariamentioning
confidence: 99%
“…9,10,13) We also reported that a pDNA/PEI/γ-polyglutamic acid complex, which also induced strong gene expression (more than 1×10 6 RLU/g tissue) in the spleen, was an effective DNA vaccine against malaria and melanoma. 27,28) pDNA/PEI/DOPS complex also showed gene expression at about 1×10 6 RLU/g tissue in the spleen. The pDNA/PEI/DOPS complex might be effective as DNA vaccine, although further study is necessary.…”
Section: 23)mentioning
confidence: 95%